2023
DOI: 10.3390/plants12061404
|View full text |Cite
|
Sign up to set email alerts
|

Time Effects of Global Change on Forest Productivity in China from 2001 to 2017

Abstract: With global warming, the concentrations of fine particulate matter (PM2.5) and greenhouse gases, such as CO2, are increasing. However, it is still unknown whether these increases will affect vegetation productivity. Exploring the impacts of global warming on net primary productivity (NPP) will help us understand how ecosystem function responds to climate change in China. Using the Carnegie-Ames-Stanford Approach (CASA) ecosystem model based on remote sensing, we investigated the spatiotemporal changes in NPP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…To examine the contribution of both abiotic and biotic factors to the spatial variation in BGBP and to account for the impact of random effects on biomass allocation, we utilized a linear mixed-effects model. The goodness of fit for these models was evaluated using the marginal R 2 value [ 44 ]. Climatic factors included the Mean Annual Temperature (MAT), Mean Annual Precipitation (MAP), Mean Hottest Monthly Temperature (MAHT), Mean Coldest Monthly Temperature (MCMT), and Annual Sunshine Duration (ASD).…”
Section: Methodsmentioning
confidence: 99%
“…To examine the contribution of both abiotic and biotic factors to the spatial variation in BGBP and to account for the impact of random effects on biomass allocation, we utilized a linear mixed-effects model. The goodness of fit for these models was evaluated using the marginal R 2 value [ 44 ]. Climatic factors included the Mean Annual Temperature (MAT), Mean Annual Precipitation (MAP), Mean Hottest Monthly Temperature (MAHT), Mean Coldest Monthly Temperature (MCMT), and Annual Sunshine Duration (ASD).…”
Section: Methodsmentioning
confidence: 99%
“…For example, higher temperatures can stimulate plant metabolism and increase photosynthetic rates and NPP ( Piao et al., 2019 ; He et al., 2022 ). Wang et al. (2023) found that NPP in Chinese forests showed a significant positive correlation with both mean annual temperature and mean annual precipitation, but this positive correlation gradually weakened over time.…”
Section: Introductionmentioning
confidence: 95%
“…For example, higher temperatures can stimulate plant metabolism and increase photosynthetic rates and NPP (Piao et al, 2019;He et al, 2022). Wang et al (2023) found that NPP in Chinese forests showed a significant positive correlation with both mean annual temperature and mean annual precipitation, but this positive correlation gradually weakened over time. In addition, all plant phenological changes are almost highly correlated with temperature changes, especially in the months before seasonal life cycle events (Peñuelas and Filella, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Functional plant traits play an essential role in exploring vegetation productivity and mitigating air pollution. Urban green spaces composed of various functional trait plants help to reduce air pollution levels [14] and serve as an important factor affecting urban ecosystem productivity [15,16].…”
mentioning
confidence: 99%